2010
DOI: 10.3390/d2020256
|View full text |Cite
|
Sign up to set email alerts
|

The Historical Ecology of Human and Wild Primate Malarias in the New World

Abstract: Abstract:The origin and subsequent proliferation of malarias capable of infecting humans in South America remain unclear, particularly with respect to the role of Neotropical monkeys in the infectious chain. The evidence to date will be reviewed for Pre-Columbian human malaria, introduction with colonization, zoonotic transfer from cebid monkeys, and anthroponotic transfer to monkeys. Cultural behaviors (primate hunting and pet-keeping) and ecological changes favorable to proliferation of mosquito vectors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 127 publications
0
20
0
1
Order By: Relevance
“…Furthermore, they found that the Fonseca MRA-353 strain of P. simium carried the Old World-type sequence and speculated that P. simium and the P. vivax populations that currently circulate among humans in the Americas entered the continent on two separate occasions that were most likely from different source populations 12 . Cormier 13 further hypothesized that East Asian migrants might have introduced Old World P. vivax / P. simium lineages into the Atlantic Coast of Brazil in the early 1800s. However, subsequent analyses revealed both New World and Old-World types of 18 S rRNA gene sequences in parasites from the Amazon Basin of Brazil and from Sri Lanka (Supplementary Text 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they found that the Fonseca MRA-353 strain of P. simium carried the Old World-type sequence and speculated that P. simium and the P. vivax populations that currently circulate among humans in the Americas entered the continent on two separate occasions that were most likely from different source populations 12 . Cormier 13 further hypothesized that East Asian migrants might have introduced Old World P. vivax / P. simium lineages into the Atlantic Coast of Brazil in the early 1800s. However, subsequent analyses revealed both New World and Old-World types of 18 S rRNA gene sequences in parasites from the Amazon Basin of Brazil and from Sri Lanka (Supplementary Text 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all of them lack DARC, a key receptor for red blood cell invasion by P. vivax , and are therefore virtually resistant to blood-stage infection with this species 11 . Parasites may also have entered the New World in pre- and post-Columbian times with migrants from the Asian mainland and the Western Pacific 3 , 12 , 13 , further contributing to the surprisingly high genetic diversity of P. vivax in the Americas 14 17 . Archaeological evidence for infection with P. vivax in pre-Columbian Native Americans is currently limited to a single report of species-specific antigens visualized by immunohistochemistry in South American mummies dating from 3,000 to 600 years ago 18 , but confirmation of P. vivax infection with more specific molecular techniques is still required 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the parasite is able to complete the cycle in monkeys, as demonstrated experimentally in monkeys of the family Aotidae [26,27] and Cebidae [28,29], it is likely that the monkeys found naturally infected by P. falciparum are able to infect mosquitoes and hence maintain the parasite in the wild and eventually back to humans. This type of infection might be frequent as suggested [30] and the possibility that New World monkeys being reservoirs of falciparum malaria as well as of other malarias, cannot thus be discarded.…”
Section: Discussionmentioning
confidence: 99%
“…Por várias décadas, estudiosos tem-se questionado se a malária humana estava presente nas Américas antes ou depois da colonização européia (BRUCE-CHWATT, 1965;CARTER;MENDIS, 2002;SINGER, 2005;CORMIER, 2010). Existem hipóteses que afirmam que a introdução deste parasito no continemente americano aconteceu em diferentes momentos, pré-colonização juntamente com a migração humana e pós-colonização, com a vinda dos europeus para as Américas e com o comércio transatlântico de escravos africanos.…”
Section: Malária Nas Américas: Introdução Precoce Ou Tardiaunclassified